The evolutionary scenario of hepatocellular carcinoma in Italy: an update. (17th August 2016) - Bucci, Laura; Garuti, Francesca; Lenzi, Barbara; Pecorelli, Anna; Farinati, Fabio; Giannini, Edoardo G.; Granito, Alessandro; Ciccarese, Francesca; Rapaccini, Gian Lodovico; Di Marco, Maria; Caturelli, Eugenio; Zoli, Marco; et al.
Abstract : Background & Aims: Epidemiology of hepatocellular carcinoma is changing worldwide. This study aimed at evaluating the changing scenario of aetiology, presentation, management and prognosis of hepatocellular carcinoma in Italy during the last 15 years. Methods: Retrospective analysis of the ITA.LI.CA (Italian Liver Cancer) database including 5192 hepatocellular carcinoma patients managed in 24 centres from 2000 to 2014. Patients were divided into three groups according to the date of cancer diagnosis (2000–2004, 2005–2009 and 2010–2014). Results: The main results were as follows: (i) progressive patient aging; (ii) progressive expansion of non‐viral cases and, namely, of "metabolic" hepatocellular carcinomas; (iii) increasing proportion of hepatocellular carcinoma diagnosed during a correct (semi‐annual) surveillance programme; (iv) favourable cancer stage migration; (v) increased use of radiofrequency ablation to the detriment of percutaneous ethanol injection; (vi) improved outcomes of ablative and transarterial treatments; (vii) improved overall survival (adjusted for the lead time in surveyed patients), particularly after 2009, of both viral and non‐viral patients presenting with an early‐ or intermediate‐stage hepatocellular carcinoma. Conclusions: During the last 15 years several aetiological and clinical features of hepatocellular carcinoma patients have changed, as their management. The observed improvement of overall survival was owing both to the wider use of semi‐annual surveillance, expanding the proportion of tumours that qualified for curative treatments, and to the improved outcome of loco‐regional treatments.